2019
DOI: 10.1002/jcp.28659
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits high glucose‐induced angiogenesis via inhibiting autophagy in RF/6A cells

Abstract: Adiponectin, one of the adipose-derived hormone with metabolic activity, has been reported to conversely affect angiogenesis of endothelial cells in vitro. The previous study in animal models has demonstrated that adiponectin has a protective role in retinal vascular injury following pathological stimuli. However, clinical research regarding the relationship between plasma adiponectin level and diabetic retinopathy (DR) are inconclusive. The aim of this study was to investigate the effect of adiponectin on hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 54 publications
2
26
0
Order By: Relevance
“…Similarly, Li et al (107) found that the exposure of RF/6A cells to HG (25 mM) inhibited cell proliferation, and promoted tube formation and cell migration, suggesting accelerated angiogenesis. Autophagy was induced in HG, revealed as increased LC3B fluorescent dots and enhanced level of LC3II/I, ATG5 proteins as well as downregulated p62.…”
Section: Autophagy Deteriorates the Neovascularization And Vascular Dmentioning
confidence: 84%
“…Similarly, Li et al (107) found that the exposure of RF/6A cells to HG (25 mM) inhibited cell proliferation, and promoted tube formation and cell migration, suggesting accelerated angiogenesis. Autophagy was induced in HG, revealed as increased LC3B fluorescent dots and enhanced level of LC3II/I, ATG5 proteins as well as downregulated p62.…”
Section: Autophagy Deteriorates the Neovascularization And Vascular Dmentioning
confidence: 84%
“…Therefore, other mechanisms of neovascularization are worth exploring. In our previous studies, we have found that anti-VEGF can activate autophagy in vascular endothelial cells, and the weakening of antiangiogenic effect may be related to the activation of autophagy [21][22][23]. However, the detailed mechanism is not clear.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, chorioretinal EC (RF/6A) was used as the main cell model for retinopathy and cultured under high glucose conditions to mimic the environment of high blood glucose. Although the endothelial characteristics of RF/6A cells were questioned [ 19 ], abundant literature shows that RF/6A cells are still used as endothelial cell lines to model retinal and choroidal angiogenesis [ 20 , 21 , 22 , 23 , 24 ]. Culturing ECs under high-glucose conditions cannot mimic all characteristics of DM but might explain the endothelial growth factor autocrine mechanism of the ECs [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%